2007
DOI: 10.1111/j.1365-2672.2006.03182.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo gene delivery and expression by bacteriophage lambda vectors

Abstract: Aims Bacteriophage vectors have potential as gene transfer and vaccine delivery vectors because of their low cost, safety and physical stability. However, little is known concerning phage-mediated gene transfer in mammalian hosts. We therefore performed experiments to examine phage-mediated gene transfer in vivo . Methods and Results Mice were inoculated with recombinant lambda phage containing a mammalian expression cassette encoding firefly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 48 publications
2
45
0
3
Order By: Relevance
“…Lambda bacteriophages are used in gene transfer and vaccine delivery because of their capacity to transduce mammalian cells in vivo 10 . Tyler and collaborators recently showed that prophage induction is required for renal disease and lethality in the EHEC mouse model, suggesting that free bacteriophages encoding Stx may play a direct role in the disease 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Lambda bacteriophages are used in gene transfer and vaccine delivery because of their capacity to transduce mammalian cells in vivo 10 . Tyler and collaborators recently showed that prophage induction is required for renal disease and lethality in the EHEC mouse model, suggesting that free bacteriophages encoding Stx may play a direct role in the disease 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Bacteriophages are also stable, compatible with simple storage and formulation methods, inexpensive to produce, and suitable for large-scale production and have an established safety record for use in humans (11). Therefore, if successful, this expression system could potentially lead to development of an easily implementable and economical strategy for the prevention of HIV infection across mucosal membranes.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicate that even unmodified nontargeted -phage particles can mediate in vivo gene delivery, possibly due to their uptake by AP cells. Addressing the mechanism of phage-mediated gene transfer, and to test whether phagocytosis was required for this process, the findings by Lankes et al [21] showed phagocytosis to be responsible for a portion but not the majority of phage-mediated gene transfer. It is more likely that nonphagocytic mechanisms contribute to the uptake of phage particles and expression of phageencoded proteins.…”
Section: Discussionmentioning
confidence: 99%